RECEPTION OF THE BIOGRAPHICAL METHOD IN HISTORICAL AND ANTHROPOGICAL STUDIES - T. I. Vlasova; G. G. Krivtchik (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. To update the question of using the biographical method and establishing its interrelation with other scientific methods and methodological principles in historical and anthropological research. Theoretical basis. Consideration of the biographical method in historical and anthropological studios carried out in the course of the general theoretical "renaissance" of classical humanitarianism, which is largely due to the uncertainty and ambiguity of theoretical discourses and discursive practices of postmodernism, pose to the researcher a number of new tasks. Among them there is "discovery of the implicit" i.e. not just the description of the results of human cultural activity in the immediate given, but the disclosure of sometimes unconscious mechanisms of this activity, of the deep "springs" of culture that ensure its movement. Originality. The authors of this research do not touch on the sociological issues of biographical research, which are widely represented in the writings of contemporary Western researchers. The subject of our message is a biographical method that is genetically derived from Ch. A. Sainte-Beuve, who believed that the main task of the biographer is to carry out an analysis of the personality of a prominent person. The research in the realm of humanities in general and in civil history in particular should take into account not only the changes in the sociocultural aspects of being, but also the corresponding transformation of methodological approaches to the analysis of the epiphenomena of "fluid modernity". This obvious fact led us to an understanding of the need for a historiosophical study of the problem of reception of a biographical method in historical and anthropological works with the subsequent historical, philosophical, cultural representation of the biographical method. Conclusions. The historiosophical transformations of the last decades, with their radical change in concepts, methods and techniques, return the researcher to the improvement of the biographical methodology that today represents anthropocentrism, which fills the science with humanistic content. The use of this methodology requires from a scientist to adhere to the basic methodological principles and mastering other scientific methods, primarily dialectics.